Prevention and Management of Operating Room Fire: An Interprofessional Operating Room Team Simulation Case - Christine L. Mai; Praelada Wongsirimeteekul; Emil Petrusa; Rebecca Minehart; Maureen Hemingway; May Pian-Smith; Ersne Eromo; Roy Phitayakorn (Association of American Medical Colleges, 2020)
Introduction Operating room (OR) fire can be a devastating and costly event to patients and health care providers. Prevention and effective management of such fires may present difficulties even for experienced OR staff. Methods This simulation involved a 52-year-old man presenting for excisional biopsy of a cervical lymph node to be performed under sedation. Participants were expected to identify and manage both contained and uncontained fires resulting from ignition by electrosurgical cautery. We conducted weekly multidisciplinary simulations in the mock OR at Massachusetts General Hospital. Participants included surgery and anesthesiology residents, certified registered nurse anesthetists, registered nurses, and surgical technicians. Participants were unaware of the scenario content. Each 90-minute session was divided into three parts: an orientation (10 minutes), the case with rapid cycle debriefing (65 minutes), and a final debriefing with course evaluations (15 minutes). Equipment consisted of a simulation OR with general surgery supplies, general anesthesia equipment, a high-fidelity Laerdal SimMan 3G simulator, a code cart, a defibrillator, dry ice for smoke effects, and a projector with a fire image. Results From April to June 2015, 86 participants completed this simulation. Participants reported that the simulation scenario was realistic (80%), was relevant to their clinical practice (93%), changed their practice (82%), and promoted teamwork (80%). Discussion Prevention and management of OR fire require collaboration and prompt coordination between anesthesiologists, surgeons, and nurses. This simulation case scenario was implemented to train multidisciplinary learners in the identification and crisis management of such an event.